Understanding Consumer Decisions to Continue Using e-Wallets in Jabodetabek - Risqiani, Renny; Lukito, Nico; Fatia, Amalia (Business and Entrepreneurial Review, 2024)
The development of internet technology makes human activities easier and faster. One form of technological innovation in the financial sector is an electronic wallet (e-wallet) online payment system. At the beginning of its launch, some e-wallets provided consumers with massive promotions (spend money). However, currently, massive promotions are no longer offered by some e-wallets. This study aims to examine consumer intentions to continue using e-wallets even though the company currently no longer provides promotions as before. Adopting the Post Acceptance Model (PAM) to determine consumer sustainability factors when using information systems. This is achieved by examining the variables that affect satisfaction and the impact of satisfaction on the value of continued use of information systems on e-wallet applications.  A total of 307 samples were collected by purposive sampling of e-wallet users who live or work in Jabodetabek. The data analysis method uses structural equation modeling. The results showed that satisfaction could influence the desire to continue using the e-wallet application felt after use, the perceived benefits received (perceived usefulness), and the enjoyment or pleasure felt in using the e-wallet application.